Damage assessment of structures VIII : selected, peer reviewed papers from the 8th International Conference on Damage Assessment of Structures (DAMAS 2009) Bejing, China, 3rd to 5th August 2009 - International Conference on Damage Assessment of Structures (7th : 2007 : Turin, Italy); Chu, F. (Stafa-Zurich, Switzerland ; Enfield, NH : Trans Tech Publications Ltd.)
Includes bibliographical references and index